Resolution of anti-GAD-associated autoimmune encephalitis in patients treated with efgartigimod - Chen, Min; Bi, Zhuajin; Kang, Wenzhong; Liu, Ruihan; Hongbo, Liu; Jiang, Yan; Wang, Qun (Frontiers in Neurology, 2025)
IntroductionTemporal lobe epilepsy (TLE) is a significant clinical phenotype of anti-glutamic acid decarboxylase (GAD)-associated disease, which is characterized by disturbances in GABAergic inhibitory neurotransmission. Efgartigimod, a neonatal crystallizable fragment receptor antagonist, controls the trafficking and recycling of pathogenic anti-GAD immunoglobulin G, showing promise as a therapeutic target.MethodsWe present a case report involving the treatment of three patients affected by GAD-seropositive autoimmune encephalitis with efgartigimod. The patients’ overall disability was assessed using the modified Rankin scale.ResultsAfter 4 weeks of efgartigimod treatment, the patients demonstrated substantial improvements, including no dementia or behavioral abnormalities and well-controlled seizures.DiscussionOur findings suggest that efgartigimod is a potential candidate drug for the treatment of anti-GADassociated autoimmune encephalitis, particularly in patients presenting with TLE.